The Effectiveness Of Kids Song In Understanding Vocabulary To Improve Students’ Motivation In Studying English, A Case Of Grade VIII Student At SMP N 1 Kayen In Academic Year 2022/2023 - Wahyu Dewi Pratiwi (STIKes Ibnu Sina Ajibarang, 2023)
An English teacher is required to be creative in creating an easy and enjoyable learning process, especially for junior high school students. Students become more motivated to learn English by using various children's songs as media. One of the learning strategies used by teachers is the use of songs. The aim of this research is to motivate and determine students' ability to understand vocabulary with examples of effective children's songs. The benefits of using children's songs include many different media such as pictures, videos, and sounds. Students must learn new vocabulary because vocabulary is an important aspect of learning English. This study uses a quantitative approach. The research results show that the use of children's songs is very significant because students like them and are effective for learning English. The use of children's songs to learn English shows that songs can motivate children's enthusiasm for learning English because learning is fun and does not feel stiff. As for the steps taken to create effective English learning, English teachers should pay attention to several aspects, type of song, and the number of students. , a type of learning activity with songs